UJI BIODEGRADASI FILEM PLASTIK CAMPURAN POLISTIREN DENGAN POLI(3 HIDROKSIBUTIRAT-KO-3-HIDROKSIVALERAT) DALAM LUMPUR - Dewi, Asiska Permata; Octaviani, Melzi; Rustini, Rustini; Zaini, Erizal; Djamaan, Akmal (Jurnal Sains dan Teknologi Farmasi, 2012)
An assay of biodegradation of plastic film combination of polystyrene (PS) and poli (3-hydroxy butyrate-ko-3-hydroxyvalerate) [P(3HB-ko-3HV)] has been conducted. The assay was done by using soil burial test method. The plastic film was made by blending technique of various composition of PS/P(3HB-ko-3HV) in to the mud. The remaining weight of plastic film was determined gravimentically time intervals 1,2,3,4 and 5 weeks of burial. Result showed that the P(3HB-ko-3HV) had an influence on the degradation rate of plastic film. The biodegradation rate increased with an increase in P(3HB-ko-3HV) content in the mixture. The rate was derived from linear regression equation and parameters such as biodegradation rate constant (k), t 50 % and t 95% were obtained. It was found that for combination of Â PS/P(3HB-ko-3HV) 95:5 k= 1,26% b/b per week , t 50 % = 39,07 weeks and t 95 % = 74,783 week for the mixture of PS/P(3HB-ko-3HV) 90:10Â  k = 1,604 % b/b per week, t 50 % = 30,57 week and t 95 % = 58,62 week. For the mixture of PS/P(3HB-ko-3HV), 85:15 k = 2,663 % b/b per week, t 50 % = 17,95 week and t 95 % = 34,85 week. While those of pure PS plastic film k = 0,24 % b/b per week, t 50 % = 201,85 week and t 95 % = 354,55 week which indicated a very slow biodegradation. Analysis by SEM showed that the surface of plastic film was eroded and damaged during the burial. The amount of bacterial colony per 1 gram of mud was 2,31x107.